Identifying skills needs for improving the engagement of the communities in the housing market renewal process: a case study of neighbourhood facilities in Northwest England - Kasim, Rozilah (2007)
In the late 1990s, several areas in Northwest of England were identified as suffering from social and economic deprivations with low housing demand, abandoned neighbourhoods, where local people and services have moved out. To address these problems, the HMR initiative was introduced by the Department of Communities and Local Government in 2003. Nine Pathfinders supported by the HMR Funds were established aimed at rebuilding communities through creating places where people want to live and work for the present and for future generations. This puts local communities at a centre of the programme and they should act themselves as agents for HMR. The Government has recognised that community engagement is vital to the success of the HMR process. What little written guidance is available from the Government for community engagement in the HMR process is inaccessible or unused in HMR. However, the local protests on the way that the HMR is being delivered suggest that local communities are not fully engaged, and highlights that the Pathfinders need the necessary skills for improving the engagement with local communities in the HMR process. The Egan report (which is further supported by the professionals in built environment) has recognised the need for considering new skills and ways of working in delivering sustainable communities. However, the report does not specifically address how these skills need to be allocated among different stakeholders. It also fails to describe the skills necessary to improve engagement with the communities. This study aims to critically appraise Government policies for community engagement practice in the HMR process, and investigate the skills needed for attaining the full level of community engagement in the HMR process. It explores the roles of key stakeholders and their levels of involvement in the community engagement process; barriers for attaining the full level of community engagement; and the stakeholders' expectations from the engagement process that leads to the skills needs for improving the engagement of communities. The study applies qualitative research within a nested research methodology with two phases of case study design (an exploratory study at Elevate East Lancashire Pathfinder, Blackburn Borough Council and Bank Top; and a detailed case study in Bank Top, Blackburn). Rigorous data collection and analysis using Nvivo is employed. Research findings from the exploratory study confinn that local communities were poorly engaged in the HMR process. This stimulated a definition of the research questions. A framework for identifying the skills needed for attaining the full level of community engagement was further developed and applied for a new play area in Bank Top. Findings from the case study identify the skills needed for attaining the full level of community engagement in the HMR process aimed at consulting young people and show some engagement, but this did not really empower the community. This study generates new knowledge about the skills needs for attaining the full level of community engagement in the HMR process. This study also offers a methodological contribution that could be applied to a similar study for different community groups and different Pathfinder areas.